Odpowiedzi

2010-03-29T22:09:49+02:00
Uprośc wyrażenia:
a) (a-b/a+b + a+b/a-b)(a²+b²/2ab + 1)* ab/a²+b²
[(a-b)²+(a+b)²/(a+b)(a-b)](a²+b²/2ab + 1)ab/(a²+b²)=
(a²-2ab+b²+a²+2ab+b²)/(a+b)(a-b)](1/2ab + 1)ab/1=
(2a²+2b²)/(a+b)(a-b)](1+2ab/2ab)ab/1=
(a²+b²)/(a+b)(a-b)](1+2ab)=
(a²+b²)(1+2ab)/(a+b)(a-b)

zał: a≠b, a≠-b
b) a-c/a²+ac+c² * a³-c³/a²b-bc²( 1 + c/a-c - 1+c/c) : :c(1+c)-a/bc=
a-c/a²+ac+c² * a³-c³/b(a²-c²)( 1 + c/a-c - 1+c/c) : :c(1+c)-a/bc=
a-c/a²+ac+c² * a²+ac+c²/b(a+c)( a-c/a-c + c/a-c - 1+c/c) : :c(1+c)-a/bc=
a-c/1 * 1/b(a+c)( a/a-c - 1+c/c) : :c(1+c)-a/bc=
(a-c)/b(a+c)*( ac/c(a-c) - (1+c)(a-c)/c(a-c)) : :c(1+c)-a/bc=
(a-c)/b(a+c)*( ac- (a-c+ca-c²)/c(a-c)) : :c(1+c)-a/bc=
(a-c)/b(a+c)*( ac-a+c-ca+c²)/c(a-c)) : :(c+c²-a)/bc=
(a-c)/b(a+c)*( -a+c+c²)/c(a-c))*bc/(c+c²-a)=
(a-c)/b(a+c)*1/c(a-c)) *bc/1=
(a-c)/b(a+c)*bc/c(a-c))=
(a-c)/(a+c) *1/(a-c)=
1/(a+c)
zał: a≠-c , a²+ac+c²≠0 ; b≠0c≠0; c+c²-a≠0 a≠c